2021
DOI: 10.3390/genes12101632
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase (hTERT) Overexpression Reveals a Promising Prognostic Biomarker and Therapeutical Target in Different Clinical Subtypes of Pediatric Acute Lymphoblastic Leukaemia

Abstract: Acute Lymphoblastic Leukemia (ALL) is a neoplasm of the hematopoietic system defined as a clonal expansion of an abnormal lymphoid precursor cell. It mostly affects children under five years of age and is the most common tumor to afflict pediatric patients. The expression of the human telomerase gene (hTERT) in patients with ALL has been studied as a biomarker and could become a new therapeutic target. We evaluate the role of hTERT gene expression in ALL pediatric patients, through quantitative real-time PCR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…There have been numerous studies on the relationship between TL and the prognosis of ALL. In B-ALL patients, high telomerase activity, elevated telomere reverse transcriptase (TERT) expression, and telomere shortening were closely associated with poor prognosis [ 20 , 21 ]. However, some studies have also found that telomere elongation was linked to poor prognosis in ALL [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies on the relationship between TL and the prognosis of ALL. In B-ALL patients, high telomerase activity, elevated telomere reverse transcriptase (TERT) expression, and telomere shortening were closely associated with poor prognosis [ 20 , 21 ]. However, some studies have also found that telomere elongation was linked to poor prognosis in ALL [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, small telomere and telomerase activities have been reported as potential biomarkers in different oncological patients [ 42 , 43 , 44 ]. Furthermore, telomere maintenance and hTERT expression are being considered as potential targets in leukemia [ 45 , 46 , 47 ]. In this context, the relevance of using biomarkers to understand B-acute lymphoblastic leukemia, as well as for guiding therapies, is evident.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase can block apoptosis mechanisms in leukemic blasts, resulting in faster disease progression, and its activities are related with lactate dehydrogenase, which is an unfavorable prognostic factor for ALL patients [ 166 ]. In this sense, recent studies have revealed telomerase overexpression and hTERT methylation status as a promising prognostic biomarkers in B-ALL (especially for childhood disease), and more precisely for maintenance and disease persistence, also reinforcing the potential of telomerase as therapeutical target, mainly due to its multiple non-canonical actions [ 45 , 47 , 179 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WRAP53 implication in leukemias was suggested by Nogueira et al [ 82 ], in which the overexpression of TERT in patients with acute lymphoblastic leukemia (ALL) proved to be a common biomarker indifferent to the ALL subtype. In addition, WRAP53 showed a strong interaction with TERT in a protein–protein interaction (PPI) network.…”
Section: Wrap53 Characterization and Cellular Rolesmentioning
confidence: 99%